Projeto Pintando as Brincadeiras: Protagonismo Infantil em Foco - Lousada, Evellyn de Souza; Riboli, Ana Barros do Nascimento; Madureira, Jane Rodrigues; Almeida, Lizie Davoglio Correa de; Alves, Paula Valeria da Costa (Anais Estendidos do Seminário de Educação (SemiEdu), 2024)
Este artigo não possui um resumo.